PROPERTIES AND MANAGEMENT IMPLICATIONS OF SOILS FORMED FROM VOLCANIC MATERIALS IN LEMBANG AREA, WEST JAVA - Edi Yatno; Siti Zauyah (Indonesian Journal of Agricultural Science, 2008)
Soils formed from volcanic materials have a high potential for agricultural development, especially for horticultural crops, tea, and pine trees. Data on the characteristics of these soils are important for the management planning. Six representative soil profiles developed on andesitic volcanic ash and tuff in Lembang area, West Java were studied to determine the soil physical, chemical, and mineralogical properties, to study the relationship between the soil properties, and to classify the soils according to the Soil Taxonomy. The results indicated that all the soils had very deep (>150 cm) solum. In general, the volcanic ash soils were darker colored, more granular, more friable, less sticky and less plastic than the volcanic tuff soils. Physically, the ash soils had lower bulk density (0.44-0.73 mg m-3) and higher available water content (13-33%) than the tuff soils. Bulk density decreased with increasing allophane. Chemically, the ash soils had higher pHNaF (mostly > 10), higher organic carbon (4.3-6.8% in upper horizons), higher CEC (20- 44 cmolc kg-1), and higher P retention (> 85%) than the tuff soils. P retention logarithmically increased with increasing oxalate extractable Al and allophane. The sand fractions of the ash soils were dominated by hornblende, while the tuff soils were predominantly composed of opaque minerals. In the clay fractions, the ash soils were dominated by allophane, whereas the tuff soils showed high contents of gibbsite and metahalloysite. Soils developed on volcanic ash were classified as Thaptic Hapludands and Typic Melanudands, while soils formed from volcanic tuff were classified as Andic Dystrudepts. The low bulk density and friable consistency of the soils contributed to favorable soil tilth. However, high P retention and Al saturation in most soils are limiting factors for plant growth. Application of P fertilizers and liming coupled with efficient placement can be recommended to enhance P availability and reduce Al toxicity. Organic matter can be used to reduce Al toxicity. Soil conservation needs to be considered, especially in the steep slope areas.